Pengaruh Kompres Air Hangat Parutan Jahe terhadap Penurunan Nyeri Arthritis Rheumatoid pada Wanita Menopause - Bela Purnama Dewi; Ika Aprilia Utami (Jurnal Kesehatan Saelmakers PERDANA, 2023)
The majority of postmenopausal women (90.32%) complained of discomfort in the bones, joints and muscles. Generally it is mostly found in the joints of the feet and joints of the hands which can cause pain which is often inflamed and described as complaints and disorders that can be said to be Rheumatoid Arthritis. This complementary treatment that uses warm compresses with grated ginger to reduce pain in rheumatoid arthritis can be done by nurses independently without collaboration with other medical teams. Warm water compresses with grated ginger can reduce pain in menopausal women who experience rheumatoid arthritis because ginger contains cyclo-oxygenase enzymes. This study aims to determine the effect of warm water compresses with grated ginger on reducing rheumatoid arthritis pain in postmenopausal women.The results of this study indicate that the average pain before applying warm compresses is 4.63 ± 5.00, while the average pain after applying warm compresses is 1.10 ± 1.00. Based on the results of statistical tests using the Wilcoxon test, it was found that ? value = 0.000, with a value of ? = 0.05 (? <?), meaning that there was an effect of warm compresses with ginger on pain intensity in postmenopausal women with rheumatoid arthritis at RT 02 Talang Jambe Palembang City in 2023